Germline BAP1 mutation in a family with high incidence of multiple primary cancers and a potential gene–environment interaction. Issue 2 (28th December 2015) - Cheung, Mitchell; Kadariya, Yuwaraj; Talarchek, Jacqueline; Pei, Jianming; Ohar, Jill A.; Kayaleh, Omar R.; Testa, Joseph R.
Highlights: Six members of a BAP1 syndrome family developed two or more primary tumors. Mesotheliomas, melanomas, basal cell carcinomas and meningiomas predominated. A gene/environment interaction is proposed to play a role in this high-risk family. Abstract: We report a high-risk cancer family with multiple mesotheliomas, cutaneous melanomas, basal cell carcinomas, and meningiomas segregating with a germline nonsense mutation in BAP1 (c.1938T>A; p.Y646X). Notably, most (four of five) mesotheliomas were peritoneal rather than the usually more common pleural form of the disease, and all five mesothelioma patients also developed second or third primary cancers, including two with meningiomas. Another family member developed both cutaneous melanoma and breast cancer. Two family members had basal cell carcinomas, and six others had melanocytic tumors, including four cutaneous melanomas, one uveal melanoma, and one benign melanocytic tumor. The family resides in a subtropical area, and several members had suspected exposure to asbestos either occupationally or in the home. We hypothesize that the concurrence of a genetic predisposing factor and environmental exposure to asbestos and UV irradiation contributed to the high incidence of multiple cancers seen in this family, specifically mesothelioma and various uveal/skin tumors, respectively.